Metafora Kata â€œHatiâ€ dalam Bahasa Melayu Riau: Analisis Semantik Kognitif (The Metaphor of the Word â€œHatiâ€ (Heart) In Malay Language of Riau: Cognitive Semantics Analysis) - Hermandra Hermandra (Jurusan Tadris Bahasa Indonesia, 2022)
This study aims to examine the metaphor of the word